Completion criteria: the tension between certainty and flexibility - Gimber, C; Shade, N (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
Completion criteria have long been an important part of closure planning because they establish levels of performance against which the success of mine closure can be assessed. However, they are often criticised as being poorly defined, making the performance expectation ambiguous, and lacking clarity that is needed for the regulator, community and the mining sector. It is best for all stakeholders when completion criteria are clear and measurable, and they provide certainty of outcomes. There has been considerable focus by the sector on improving the level of specificity in completion criteria. This is especially true in Queensland (Australia), where the progressive rehabilitation and closure plan framework requires criteria to be specified for each milestone in the rehabilitation process. However, when completion criteria become very specific and prescriptive, agility can be difficult to achieve in response to unforeseen circumstances, innovation can be stifled, and both an administrative and compliance burden can be created. Further, if the prescriptions are not correct, it is possible to achieve completion criteria and yet still have poor outcomes. There has been a shift in many jurisdictions towards outcome-based environmental regulation, recognised by the Australian government as best practice (Commonwealth of Australia 2016). The cited reasoning behind the shift is that it is the outcome that matters as it better caters for innovation and can be adjusted over time as necessary. Is it possible to adopt outcome-based completion criteria that still provide an enforceable, auditable regulatory tool? This paper explores ways that the mining sector can take the learnings from environmental regulation reform and apply those concepts to the formulation of closure completion criteria.
Keywords: outcome-based; prescriptive; completion criteria; closure planning